Towards alternative precepts of statehood in Africa : the role of traditional authorities in reconstituting governance and state in Somaliland - Wiuff Moe, Louise (Stellenbosch : Stellenbosch University, 2009)
Thesis (MA (Political Science))--Stellenbosch University, 2009.